Inovasi Produk QR Code Dan Digitalisasi Pemasaran Untuk Optimalisasi Penjualan UMKM Keripik Balado - Elisa Daniati Edison; Nency Extise Putri; Arika Juwita Z; Ikhsan Adistira (STMIK Royal, 2025)
Abstract: Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting the national economy; however, they continue to face challenges in management and digital marketing. Keripik Balado Uni Yen, a local MSME engaged in the traditional Minangkabau snack industry, experiences obstacles in expanding its market due to limited product innovation and reliance on conventional methods of promotion and sales. This condition has led to stagnant sales performance and low managerial efficiency, indicating the need for strategic efforts to enhance business capacity. This community service program aims to strengthen the competitiveness of the MSME through the development of product packaging integrated with a QR code and a point of sale system based on a website and digital cashier machine, while also promoting digital marketing adoption. The program was implemented using a participatory approach involving training, technical assistance, and continuous monitoring and evaluation of technology implementation. Digital marketing through social media proved effective in expanding market reach and increasing sales by up to 40%. Overall, the program demonstrates that integrating innovative packaging, digital systems, and online marketing serves as an effective strategy to enhance the competitiveness and sustainability of local MSMEs. Keywords: digital marketing; innovation QR code packaging; point of sales; MSMEs Abstrak: UMKM memiliki peran strategis dalam mendukung perekonomian nasional, namun masih menghadapi berbagai tantangan dalam aspek manajemen dan pemasaran digital. UMKM Keripik Balado Uni Yen merupakan UMKM lokal yang bergerak di industri makanan olahan khas Minang, menghadapi tantangan dalam memperluas pasar akibat keterbatasan inovasi produk serta masih mengandalkan metode konvensional dalam promosi dan penjualan. Kondisi ini berdampak pada stagnasi penjualan dan rendahnya efisiensi manajerial, sehingga diperlukan upaya strategis untuk meningkatkan kapasitas usaha. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan daya saing UMKM melalui pengembangan kemasan produk yang dilengkapi kode QR dan terintegrasi dengan sistem point of sale berbasis website dan mesin kasir digital, serta mendorong digitalisasi pemasaran. Kegiatan pengabdian ini dilaksanakan dengan pendekatan partisipatif melalui pelatihan, pendampingan teknis, serta monitoring dan evaluasi implementasi teknologi. Pemasaran digital melalui media sosial juga terbukti efektif memperluas jangkauan pasar dan meningkatkan penjualan hingga 40%. Secara keseluruhan, kegiatan ini menegaskan bahwa integrasi inovasi kemasan, sistem digital, dan pemasaran daring merupakan strategi efektif untuk memperkuat daya saing dan kemandirian UMKM lokal secara berkelanjutan. Kata Kunci: digitalisasi pemasaran; kemasan inovatif QR Code; point of sales; UMKM